The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/cryst8120451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Electronic Structures, and Debye Temperature of NixBy Compounds Obtained by the First Principles Calculations

Abstract: Mechanical properties, electronic properties, and Debye temperatures of Ni x B y (Ni 3 B, Ni 2 B, Ni 4 B 3 and NiB) compounds were obtained by the first principles calculations based on the density functional theory (DFT). The results showed that the formation enthalpy of the Ni x B y compounds were stable with negative formation enthalpy. NiB had the largest B, G, and E, and the smallest υ; it also had the highest hardness (10.8 GPa) and Debye temperature (681.8 K). Ni 4 B 3 had the strongest anisotropy. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Figure and Table S1 indicate that Ni 2 B, α-Ni 4 B 3 , β-Ni 4 B 3 , and NiB have negative E coh and Δ H r . It is consistent with the previous results of formation energy which demonstrate that all of these structures are stable . Moreover, α-Ni 4 B 3 is the most stable phase, followed by β-Ni 4 B 3 , Ni 2 B, and NiB.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Figure and Table S1 indicate that Ni 2 B, α-Ni 4 B 3 , β-Ni 4 B 3 , and NiB have negative E coh and Δ H r . It is consistent with the previous results of formation energy which demonstrate that all of these structures are stable . Moreover, α-Ni 4 B 3 is the most stable phase, followed by β-Ni 4 B 3 , Ni 2 B, and NiB.…”
Section: Resultssupporting
confidence: 93%
“…Thus, the Ni 3 B is not considered in this work. The skeletons of structures for Ni 2 B ( I 4 /mcm ), α-Ni 4 B 3 ( Pnma ), β-Ni 4 B 3 ( C 2 /c ), and NiB ( Cmcm ) are shown in Figure . Ni atoms can form a three-dimensional (3D) skeleton in Ni 2 B, due to the high Ni content (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, when the hardness of the samples in the table was examined, it was found that the hardness of the outer layers of the samples subjected to heat treatment at 900 ℃ and 1050 ℃ increased as the sintering time and B 4 C rate increased. In their studies, Wang et al, stated that Ni 4 B 3 phase had the strongest anisotropy and while the hardness value was 8.3 GPa for Ni 3 B phase, it was around 9.7 GPa for 8 Ni 4 B 3 phase [18]. Due to different hard phases (such as Ni 4 B 3 ) formed, the highest hardness increase was obtained from the samples sintered at 1050 ℃.…”
Section: Microhardness Testmentioning
confidence: 98%
“…Various crystal structures of these substrates contribute to their varied properties and applications in various fields. Nevertheless, nickelboron compounds, being promising functional materials, exhibit a range of appealing characteristics, including high hardness, high melting point, remarkable thermal stability, excellent catalytic, and satisfactory electronic properties [25][26][27].…”
Section: Introduction mentioning
confidence: 99%